Aplikasi Manajemen Mahasiswa PKL Diskominfo Provinsi Kalimantan Selatan Berbasis Web - Rezky Izzatul Yazidah Anwar; Tri Wahyu Qur'ana (STIKes Ibnu Sina Ajibarang, 2025)
It is Application hoped that this PKL student management application can provide significant benefits for all relevant stakeholders. By reducing the administrative burden, this application allows the management of street vendors to be more structured and efficient. The existence of a progress monitoring and reporting system also has the potential to improve the quality of PKL implementation by providing a more in-depth view of student activities. In addition, collaborative communication facilities in the application can enrich students' experiences in interacting with supervisors and fellow students, as well as support better practical learning. In conclusion, the development of this PKL student management application is an important step in increasing the effectiveness and efficiency of the PKL process at the South Kalimantan Province Diskominfo. With a focus on integration, transparency and better communication, this application has the potential to optimize the student experience during PKL and facilitate more organized management. The broader implications of this research could also impact the development of similar solutions in various educational institutions and other industries.